(untitled) (قضايا سياسية, 2022)
Iraqi society is one of the societies that suffer from poverty in women. Poverty is expressed in women more than men, and this is due to most of the society looking at it through its role in society and cultural outlook, and this is what often leads to women’s effort and hinders their entry to the labor market, along with Thus, it contributed to wars and conflict, beneficial to the decision-maker in the state, for participation in the feminization of poverty and advancemen.